A Methods engineering study on Leather Gloves Company, Incorporated - Abarquez, Joselito; Bangalan, Darwin P.; Esguerra, Kathryn L.; Inumerable, Jennifer V. (Diliman, Quezon City College of Engineering, 2002)
The group conducted a project study on Leather Gloves Company, Incorporated, a medium scale company that sells baseball and ice-hockey gloves for export. The primary aims in the course of this study were to determine the core problems of the company and to generate feasible solutions to address the root causes of these problems. Through the problem analysis done by the group, it was determined that the core problem of the company is its significant number of delays along the assembly line in their production of baseball gloves. This was found to have two verified root causes, namely : (a) WIP goods are piled up before advancing to the next process, and (b) inefficient plant layout. The former is due to the batch processing of raw materials from one station to the next. The other cause, on the other hand, is due to the inefficient arrangement of machines and workstations in the assembly section. As stated earlier, the root causes of the problem were addressed by generating and evaluating alternatives based on some given specific criteria. For the WIP material flow, three possible alternatives were evaluated : installing a conveyor belt, hiring a porter, and rearranging the layout. The latter was found to be the best among the three due to its lower cost and feasibility. For the inefficient plant layout, two new layouts were proposed for the assembly section. Layout 2 proved to be the more efficient because of its better rating based on the criteria for evaluation. In implementing layout 2 to solve the company's delay problem, a new arrangement of machines and equipment is mainly required. This in turn calls for coordinating with the Senior Industrial engineer, hiring workers to arrange the new layout, communicating the new method of transport to affected workers and employees, and formalizing the proposed layout in the company. A specific implementation plan was proposed to formalize the installation of layout 2. The results and conclusions inferred in the conduct of this project study could also be applied to the other sections and products of the company to further improve its productivity and minimize quality losses.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis